2020
DOI: 10.1021/acsami.9b13946
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Gas Sensors Based on Graphene Nanoribbons Grown by Chemical Vapor Deposition

Abstract: Despite the recent advances in bottom-up synthesis of different kinds of atomically precise graphene nanoribbons (GNRs) with very diverse physical properties, the translation of these GNRs into electronic devices remains challenging. Among other factors, the electronic characterization of GNRs is hampered by their complex synthesis that often requires custom-made organic precursors and the need for their transfer to dielectric substrates compatible with the conventional device fabrication procedures. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 70 publications
1
49
0
1
Order By: Relevance
“…Being almost ideal nanowires or nanotags, GNRs are an extremely accurate tool, promising for nanoelectronic components, ultrasensitive chemical and mechanical sensors, etc. [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Being almost ideal nanowires or nanotags, GNRs are an extremely accurate tool, promising for nanoelectronic components, ultrasensitive chemical and mechanical sensors, etc. [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the power consumption and to develop an economical setup, researchers fabricated and reported single-sensors based on selective material synthesized through earlier mentioned techniques [124,129]. These sensors generate distinct dynamic responses against different gases, and hence one sensor can be used for the identification of various gases.…”
Section: Machine Learning-based Smart Gas Sensorsmentioning
confidence: 99%
“…Therefore, it can be estimated that CWT and FFT are vital and contain much of the useful information for unique pattern generation [135]. Shekhar et al [129] reported a CVDgrown graphene nanoribbon e-nose system consisting of 38 sensors for VOC detection. The schematic diagram, output response, and LDA accuracy graphs towards different VOCs are shown in Figure 16A.…”
Section: Chemiresistive Type Smart Gas Sensors Using Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The width, edge structure, and functionalization of GNRs make it a promising candidate for electronic devices and biomedical applications [ 18 , 27 , 28 , 29 , 30 , 31 , 32 ]. The tunable physical and electronic properties of GNRs hold promising potential for the fabrication of gas sensors [ 33 ] due to the high conductivity, resistance to electro-migration due to the strong inherent carbon–carbon bonds, extraordinary mechanical strength, and large current conduction capacity [ 26 , 33 , 34 ]. The addition of GNRs into a polymer matrix can also modify the electrical, thermal, and mechanical properties of the polymer matrix due to the interfacial properties of final nanocomposite and compatibility of this nanofiller with polymer [ 28 , 35 ].…”
Section: Introductionmentioning
confidence: 99%